EVALUASI DESAIN ACUAN SEPATU MANUAL TERHADAP KENYAMANAN KAKI - Abimanyu yogadita Restu Aji; Achmad Basri; Delia Agustin Indrayanto (Politek ATK Yogyakarta Press, 2025)
The handcrafted shoe industry, or traditional shoemaking, holds significant cultural and economic value, yet still faces challenges in ergonomics and user comfort. Currently, many artisans rely on experience and intuition when creating shoe molds. Mismatches between the mold shape and the user's foot anatomy can lead to uneven pressure distribution. This study aimed to evaluate the suitability of a wooden handcrafted shoe mold design for wearer comfort. Testing was conducted by comparing the mold contour to foot anatomy data and a five-day wear test to observe user comfort responses. The evaluation results indicated that the manual mold met general size requirements for length and heel, but inaccuracies were found in the ball girth and waist arch, which tended to be narrow and asymmetrical. This condition causes excessive pressure on the instep and little toe, leading to pain and potential irritation during repeated wear. Furthermore, the less flexible nature of the upper material makes the shoe's adjustment process to the foot shape take longer and hinders even pressure distribution. Based on these findings, refinement of the mold design is needed to adjust the mold dimensions based on local anthropometric data to improve shoe comfort and ergonomic performance.